Comparison of Storet and Pollution Index Method to Assess the Environmental Pollution Status: A Case Study from Lampung Bay, Indonesia - Giri Rohmad Barokah; Farida Ariyani; Tuti Hartati Siregar (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
The determination of pollution status is an important process of environmental quality monitoring especially in strategic waters for coastal areas, such as in Lampung Bay. An effective and sensitive Water Quality Index (WQI) method is needed, to accurately determine the environmental pollution status. This study aimed to compare the sensitivity of Storage and Retrieval of Water Quality data System (STORET) and Pollution Index (PI) as a WQI method, a case study from Lampung Bay coastal waters, Indonesia.  Water quality analysis i.e. Dissolve Oxygen (DO), pH, salinity, nitrite, nitrate, phosphate and ammonia was conducted spatially (three zones of Lampung Bay; river mouth, aquaculture and bay area) and seasonally (April and October 2015). The study found that nitrate and phosphate values were exceeded the limits of water quality standard (Indonesia Ministry of Environment Decree No. 51/2004) for marine organisms. However it may still support the aquaculture activities. The two WQI methods produced different pollution status of Lampung bay. STORET was found to be more sensitive method. Pollution Index method revealed a status of moderately polluted while STORET showed heavily polluted status. Therefore, this study suggest the use of STORET index, compare to Pollution Index, in an assessment of pollution status at watershed area.